World drug report 2007 - United Nations Office on Drugs and Crime (UNODC) (2007)
Something new and significant is going on in the world drugs market. In last year's World Drug Report, we made the argument that drug control is working, and the world drug problem is being solved. This 2007 Report provides further robust evidence of this trend. For almost every kind of illicit drug - cocaine, heroin, cannabis and amphetamine - type stimulants (ATS) - there are signs of overall stability, whether we speak of cultivation, production or consumption. Hopefully, within the next few years evidence to support this claim will become statistically and logically incontrovertible. This does not mean that the drug problem has been solved or that we can become complacent. Nor is the good news universal. Progress made in some areas is often offset by negative trends elsewhere. But overall, we seem to have reached a point where the world drug situation has stabilized and been brought under control.